2003
DOI: 10.1046/j.1439-0388.2003.00400.x
|View full text |Cite
|
Sign up to set email alerts
|

Serum insulin‐like growth factor‐1 concentration in pigs divergently selected for daily food intake or lean growth rate

Abstract: Summary Divergent selection over seven generations for daily food intake (DFI) and for two lean growth rate (LGA and LGS) selection objectives in pigs produced correlated responses in serum insulin‐like growth factor‐1 (IGF‐1) concentration. The LGA and LGS selection objectives were for lean growth, but with performance testing on ad libitum (LGA) or on restricted (LGS) feeding regimes. There were 342 animals in the study, with an average of 46 pigs in each selection line and 72 pigs in the control line. All a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
2

Year Published

2005
2005
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 20 publications
2
9
2
Order By: Relevance
“…These results were consistent with estimates from Lamberson et al (1995) and QAF1, reported in Luxford et al (1998a). Poorer data structure in the remaining trials made it difficult to accurately separate additive genetic from common litter effects, as was also observed in the study of Cameron et al (2003). Overall, larger variances were observed in trials with higher mean IGF-I concentrations.…”
Section: Results and Discussion Trialsmentioning
confidence: 96%
See 1 more Smart Citation
“…These results were consistent with estimates from Lamberson et al (1995) and QAF1, reported in Luxford et al (1998a). Poorer data structure in the remaining trials made it difficult to accurately separate additive genetic from common litter effects, as was also observed in the study of Cameron et al (2003). Overall, larger variances were observed in trials with higher mean IGF-I concentrations.…”
Section: Results and Discussion Trialsmentioning
confidence: 96%
“…These results are consistent with the usual consequences of selecting for improved lean growth efficiency on meat quality traits (see Lonergan et al 2001), even without using information on IGF-I concentrations to facilitate selection decisions. Cameron et al (2003) performance tested 342 descendents of 6 selection lines and a control line, maintained without selection for the previous 5 generations, in a study involving 2 nutritional regimes. All animals were recorded for IGF-I at 6 weeks of age, at 30 kg, and at 90 kg before and after fasting.…”
Section: Results and Discussion Trialsmentioning
confidence: 99%
“…Circulating IGF-1 concentrations were significantly correlated with the body size in three types of swine, which differed in growth rate and mature body weight, suggesting that IGF-1 is involved with the in vivo regulation of swine growth . However, Cameron et al (2003) reported that serum IGF-1 was useful to predict ADFI physiologically, but not ADG and backfat depth, at six weeks of age. Studies demonstrated the relationships between plasma IGF-1 and growth performances, showing positive and negative correlation of plasma IGF-1 concentration at 25 kg BW, with estimated lean percentage at 90 kg.…”
Section: Resultsmentioning
confidence: 97%
“…Additional studies should evaluate the effects of this polymorphic microsatellite on performance traits at early ages. Effects of this polymorphism on circulating IGF1 content, that was reported to be correlated with several production traits in growing pigs (Lamberson et al, 1995;Cameron et al, 2003) should also be investigated. In addition, the implementation of a selective genotyping approach on other traits, e.g.…”
Section: Discussionmentioning
confidence: 99%
“…In pigs, blood serum IGF1 concentration has been genetically correlated with daily feed intake, residual feed intake, growth rate, lean meat deposition, back fat thickness (BFT), carcass weight and intermuscular fat content. Associations showed some differences (in some cases not fully concordant) depending on the age of the animals, the breeds/lines and the experimental designs, with potential practical applications in predicting genetic merit of the pigs (Taylor et al, 1992;Lamberson et al, 1995;Cameron et al, 2003;Te Pas et al, 2003;Suzuki et al, 2004;Lee et al, 2005;Estany et al, 2007;Hoque et al, 2009;Bunter et al, 2010). By using transgenic pigs expressing a human IGF1 cDNA, Pursel et al (2004) showed that these animals were leaner than control pigs, suggesting that expression of IGF1 in skeletal muscle altered body composition in adult pigs without any effects on growth performances.…”
Section: Introductionmentioning
confidence: 99%